Virtual reality versus face-to-face practice: a study into situational apprehension and performance. Issue 1 (2nd January 2020) - Davis, Alyssa; Linvill, Darren L.; Hodges, Larry F.; Da Costa, Albert Florencio; Lee, Alexzander
ABSTRACT: This exploratory study examines the role virtual reality can play in student speech practice for oral communication courses. The study focuses on situational communication apprehension of the virtual reality practice session in relation to students who practice face-to-face and the final grade of the subsequent speech. Test and control groups practiced their informative speech presentations for either another student or in a virtual environment. Both the test and control groups filled out the Situational Communication Apprehension Measure after their session. Student grades were also collected for participants in each group after their in-class speech presentation. The test group (virtual reality practice) was found to have significantly higher situational communication apprehension than the control group. No significant difference was found for final speech grades between the test and control groups. The significance and implications of these finding are discussed as they related to public-speaking education.